Simulations of the effects of density and temperature profile on SMBI penetration depth based on the HL-2A tokamak configuration - 吴雪科 李会东 王占辉 冯灏 周雨林 (Chinese physics B, 2017)
Using the trans-neut module of the BOUT＋＋ code, we study how the fueling penetration depth of supersonic molecular beam injection（SMBI） is affected by plasma density and temperature profiles. The plasma densities and temperatures in L-mode are initialized to be a set of linear profiles with different core plasma densities and temperatures. The plasma profiles are relaxed to a set of steady states with different core plasma densities or temperatures. For a fixed gradient, the steady profiles are characterized by the core plasma density and temperature. The SMBI is investigated based on the final steady profiles with different core plasma densities or temperatures. The simulated results suggest that the SMB injection will be blocked by dense core plasma and high-temperature plasma. Once the core plasma density is set to be N（i0）= 1.4N0（N0= 1 × 10^19m^-3） it produces a deeper penetration depth. When N（i0） is increased from 1.4N0 to 3.9N0 at intervals of 0.8N0, keeping a constant core temperature of T（e0）= 725 eV at the radial position of ψ = 0.65, the penetration depth gradually decreases. Meanwhile, when the density is fixed at N（i0）= 1.4N0 and the core plasma temperature T（e0） is set to 365 eV,the penetration depth increases. The penetration depth decreases as T（e0） is increased from 365 eV to 2759 eV. Sufficiently large N（i0） or T（e0） causes most of the injected molecules to stay in the scrape-off-layer（SOL） region, lowering the fueling efficiency.